(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This research was conducted to analyse the strengthening of the KOMASTI coffee agro-industry as a strategy to improve farmer welfare and national economic resilience through the integration of the Asta Gatra framework to achieve sustainable development. Design/methodology/approach: This study adopted a mixed method, with data obtained through in-depth interviews, focus group discussions, and field surveys with coffee farmers and agro-industry players in Dairi Regency, North Sumatra. Analysis of product value addition was done based on the Hayami model to determine production efficiency and distribution of economic value throughout the supply chain. Findings: The Komasti coffee agroindustry records a value-added ratio of 47.34% and a profit margin of 97.59%, reflecting strong economic potential. Nevertheless, the proportion of value captured by farmers remains low due to rudimentary processing methods and limited market connectivity. Originality/value: This study makes theoretical and practical contributions to the literature on value chains and national resilience. The developed instrument shows that the enhancement of the local resource coffee agro-industry is a matter of both economic strategy and policy for building strong, resilient, inclusive and sustainable national resistance.